Knowledge and attitudes of health professionals regarding pain assessment and management in neonates - Verusca Kelly Capellini; Mariana Firmino Daré; Thaíla Corrêa Castral; Marialda Moreira Christoffel Christoffel; Adriana Moraes Leite; Carmen Gracinda Silvan Scochi (Universidade Federal de Goias, 2014)
Multiple factors can have an effect on pain management in neonates, which motivated us to analyze the knowledge and attitudes held by doctors, nurses and nursing assistants who work in neonatal units in a hospital in the state of São Paulo, Brazil, regarding neonatal pain assessment and management. This study is descriptive and was conducted with 57 health professionals. The results of the questionnaires revealed that only one professional believed that neonates do not feel pain, and 53 professionals stated the contrary, but were not familiar with neonate pain assessment scales. Professionals indicated fentanyl and midazolam as adequate analgesics for acute pain. Umbilical catheterization, gastric probing and heel pad puncture were considered painful procedures and indications for the use of analgesia.  Health professionals are knowledgeable about pain in neonates, but this knowledge is not reflected in clinical practice. It is essential for professionals to be trained regarding knowledge transfer so that neonate pain assessment and management can be implemented. doi: 10.5216/ree.v16i2.23611.